Prevalence of natal teeth in newborn babies in Isfahan during a one-year period - Maryam Hajenorouzali Tehrani; Hajar Sekhavati; Mansour Javeri (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: Natal teeth are present at the time of birth. The etiology of these teeth is still unknown but some investigators suggest the association of these teeth with various syndromes or developmental disorders. The aim of present study was to evaluate the prevalence of natal teeth in newborn babies in Isfahan.Materials and Methods: This cross-sectional descriptive/analytical study evaluated all the infants born from August 1997 to August 1998. Data was collected by questionnaires, which included data such as birth date, gender, height and weight at the birth, number of natal teeth and their location, history of natal teeth in the family, state of the nervous, cardiovascular and genital system and developmental disorders. Data was analyzed using Pearson's and chi-squared tests (p value ≤ 0.05). Results: A total of 31940 infants were born during the period in Isfahan. A total of 26 natal teeth were found in 17 newborn babies; therefore, the prevalence of natal teeth in Isfahan was 1 in 1878 births. 58.8% of the infants with natal teeth were male and 41.2% were female, with significant gender preference for males (p value < 0.05). Of the 24 natal teeth 92.30% were lower central incisors, 60% of which were bilateral, followed by maxillary central incisors and molars (3.84% each). Six infants with neonatal teeth had a family history of such teeth, which was statistically significant (p value < 0.05). None of the infants with natal teeth had developmental disorders or syndromes.Conclusion: Natal teeth are not very common. However, knowledge about how to manage these structures is essential for the general well-being of the child. Further studies on different ethnic groups are required to better understand etiology and nature of natal teeth. Key words: Newborn, Natal tooth, Prevalence.